Adenovirus infections in dogs: diagnostic features - Mykola Radzykhovskyi; Olha Dyshkant; Bogdan Gutyj; Roman Sachuk; Yuliia Palytsia (Ukrainian Journal of Veterinary Sciences, 2022)
In the general pathology of dogs, viral diseases occupy a leading place, and infectious hepatitis, the causative agent of which is a virus of the Adenoviridae family, is of particular concern. Recently, the virus has spread to many countries around the world, which indicates changes in the properties of the pathogen. At the same time, the epizootic situation concerning infectious diseases, including adenoviruses, whose development is influenced by the mass keeping of dogs, has worsened in Ukraine. The purpose of this study is to supplement, clarify, and generalize data on epizootological features, morphological and biochemical parameters of blood and pathological and anatomical changes in type I canine adenovirus. The following research methods were used to conduct the research: epizootological analysis, clinical (determination of the general clinical condition of animals), pathological and anatomical (detection of macroscopic changes), haematological (morphological and biochemical parameters of blood) and statistical (processing of digital data to determine the probability of changes in indicators). According to the results of comprehensive studies, it was proved that dogs of different breeds, including mongrels, are susceptible to type I adenovirus, and the peak manifestation of the disease is the spring-summer period in animals aged one to two years. Infectious hepatitis is characterized by the development of erythrocytopenia, a decrease in haematocrit, leucocytosis, and lymphocytopenia. Changes in biochemical indicators are characterized by a decrease in haemoglobin, creatinine, urea, glucose in the blood, and a decrease in the activity of α-amylase and an increase in the content of total bilirubin, hyperfermentaemia of alkaline phosphatase and alanine aminotransferase. The most pronounced pathoanatomical changes are an increase in the size of the liver with the development of necrosis, and in the gastrointestinal tract-haemorrhages in the small intestine. The multisystem pathogenic effect of the virus is characterized by nephrosis, pinpoint haemorrhages in the pancreas, and inflammatory changes have been established in the lymph nodes. As a result of an experimental study of haematological parameters and pathoanatomical changes, a complex pathogenesis of the disease with multiple organ failure was established. In the study of infectious diseases of dogs, the most important aspect is clinical and diagnostic information content. Therefore, scientific research on a more profound understanding of the diagnosis of canine adenovirus will determine the algorithm for justifying the diagnosis